“National and Provinciall Churches Are Nullityes”: Henry Dunster's Puritan Argument against the Puritan Established Church - Den Hartog, Jonathan (A journal of church and state, 2014)
Cotton Mather had a problem. With his Magnalia Christi Americana, he was writing in defense of the New England Way that his grandfather (Richard Mather) and fat